Nanomaterials and Nanorobotics in Dentistry: A Review - Kasimoglu, Yelda; Tabakcilar, Derya; Guclu, Zeynep A.; Yamamoto-Nemoto, Seiko; Tuna, Elif B.; Ozen, Bugra; Tuzuner, Tamer; Ince, Gökhan (UI Scholars Hub, 2020)
Nanotechnology is a branch of science focusing on the manipulation of materials measured on the nanoscale (size = 1–100 nm). Recent advances in the field of nanodentistry have resulted in the development of alternative treatment plans for common dental problems, bringing about a paradigm shift in dentistry. Nanorobots, also known as “nanites” or “nanomachines,” are theoretical microscopic devices that may be used for the diagnosis and treatment of oral health problems. This paper aims to discuss the latest innovations in the field of nanodentistry.